THE ROLE OF ETNOSCENCE-BASED LEARNING IN IMPROVING LOCAL KNOWLEDGE OF ELEMENTARY CHILDREN - Devi Alviya; Putri Ika Cahyani; Nurhaningtyas Agustin; Irfa’i Alfian Mubaidilla (Institute Agama Islam Al-Qolam Malang, 2023)
Ethnoscience is a learning design that integrates science with local culture. When viewed from the facts on the ground, students' interest in studying science is very low, as is their knowledge of local cultures. The results of the PISA (Program for International Student Assessment) study show that on average Indonesian students have scientific literacy which is decreasing from year to year, which is 393 in 2006, 383 in 2009, and in 2012 it is 382. This study aims to describe the role of ethnoscience learning in increasing local knowledge of elementary age children. This research method uses a qualitative approach to the type of literature study. The data sources used are taken from journals and books published in the last 10 years. The results of this study indicate that learning that utilizes local wisdom as a source of learning can increase students' scientific knowledge and Local Knowledge. Local Knowledge development in learning can be done through the preparation of lesson plans, media, teaching materials, methods and models based on ethnoscience. Based on the discussion of the results and research findings, it can be concluded that every learning using media, teaching materials, methods and models based on ethnoscience can increase the Local Knowledge of elementary age children and facilitate the teaching and learning process